(untitled) (Boston, MA, 2008)
This is a guide to assessing four types of doing business in or with a particular developing country and provides strategies for capturing fast-growing consumer markets in emerging economies.
Keywords: Developing countries,Phát triển đất nước; Commerce,Thương mại